FACTOR INFLUENCING HEALTHY EATING PATTERNS AND NUTRITIONAL STATUS OF CHILDREN AGED 3-7 YEARS: LAWRENCE GREEN THEORY APPROACH - Widia Shofa Ilmiah; Rifzul Maulina; Anik Sri Purwanti (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Background: Nutrition issues among children in Indonesia remain a significant challenge, with the prevalence of stunting in children under five reaching 24.4% in 2021. Objective: This study aim to analyse the dominant factors affecting healthy eating patterns and nutritional status in children aged 3-7 years: Lawrence Green's theory approach. Material and Methods: Used observational study with a cross-sectional approach, the sample consisted of 44 children. Data collection was carried out using weight scales, microtoises, observation sheets, and food recall questionnaires. Results: Showed that the knowledge level was quite good (52.3%); family support was quite good (56.8%); children's eating patterns were mostly healthy (65.9%); children's nutritional status scored between ≥-2SD and ≤+2SD (65.9%). Heteroscedasticity scatter plot shows a certain pattern, normal PP Plots closely approach the line. Conclusion: That the most dominant factor affecting children's nutritional status is the parents' knowledge level about nutrition and children's eating patterns.